The effect of core and peripheral quality of satisfaction and loyalty of moderated patients by switching cost - Ariefin, Mesra Surya; Andarwati, Andarwati; Hadiwidjojo, Djumilah (MEC-J (Management and Economics Journal), 2019)
This study aims to examine and analyze the effect of core service quality and Peripheral service quality on patient satisfaction and loyalty at the RSUD Dr. Soegiri Lamongan which is moderated by switching costs. The number of samples in this study were 36 patients at Dr. Soegiri Lamongan. The technique of collecting data uses questionnaires, interviews, and literature studies. Data analysis in this study was SEM using PLS software. The results of this study indicate that core service quality and peripheral service quality have a significant effect on patient satisfaction, core service quality has no direct significant effect on patient loyalty, peripheral service quality has a significant effect on patient loyalty, patient satisfaction has a significant effect on patient loyalty. Patient satisfaction acts as a perfect mediation of the influence of core service quality on patient loyalty and patient satisfaction plays a role as not a mediation of the influence of peripheral service quality on patient loyalty. Switching cost strengthens the relationship between patient satisfaction and patient loyalty but is not significant.Â